JAPANESE CONDITIONAL EXPRESSIONS AND INDONESIAN EQUIVALENTS - Rianny Puspitasari; Panji Agnyoto (ReALL - Research on Applied Linguistics and Literature, 2022)
There are many things that need to be considered in the translation process, especially the disclosure of messages from the source language into the target language. The message must be in the target language's closest and most reasonable equivalent. Meanwhile, not all languages have the same equivalent or are even close to other languages. Likewise, even though Japanese and Indonesian both have these expressions in conditional expressions, it is necessary to examine the equivalents between them. This research was conducted by examining the data of conditional sentences in the novel â€œBotchanâ€ by Natsume Soseki and its translation into Indonesian. The method used is the descriptive method using the distributional study method. The way to collect data in this study is to select and separate sentences containing Japanese conditional expressions (âˆ¼To, ~Ba, ~Tara, and ~Nara) translated into Indonesian conditional expressions to become apabila, jika, kalau and seandainya, from the whole novel. Then do substitution or replacement techniques. The result of the research found is the conditional form ~to the equivalent is apabila, jika, kalau; the conditional form ~ba is apabila, jika, kalau and seandainya; the conditional form ~tara is apabila, jika, kalau and seandainya; the conditional form ~nara is apabila, jika, kalau and seandainya. Conjunctions that mean requirements, between one and another can be substituted for each other, but this can also be determined from the nuances contained in the sentence, the conjunctions apabila and jika contain more formal nuances, while kalau tends to be more neutral. As for seandainya, it means something that is unlikely to even happen.